2022
DOI: 10.3390/polym14112264
|View full text |Cite
|
Sign up to set email alerts
|

Water Treatment Using High Performance Antifouling Ultrafiltration Polyether Sulfone Membranes Incorporated with Activated Carbon

Abstract: Membrane fouling is a continued critical challenge for ultrafiltration membranes performance. In this work, polyether sulfone (PES) ultrafiltration (UF) membranes were fabricated via phase-inversion method by incorporating varying concentrations of APTMS modified activated carbon (mAC). The mAC was thoroughly characterized and the fabricated membranes were studied for their surface morphology, functional groups, contact angle, water retention, swelling (%) porosity, and water flux. The hydrophilicity of mAC me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Furthermore, researchers aimed to enhance PES membranes' functionality by providing anti-fouling protection and imparting antimicrobial properties suitable for more complex water treatment environments. In this pursuit, Abid et al [58] fabricated PES ultrafiltration membranes through a phase change method using varied concentrations of APTMS (3-Aminopropyltrimthoxysilane) modified activated carbon (mAC) (Figure 5c). The resulting mAC membranes revealed enhanced hydrophilicity, reduced contact angle, improved porosity, roughness, water retention, and heightened water flux.…”
Section: Antimicrobial and Anti-fouling Self-cleaning Of Pes Fiber Me...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, researchers aimed to enhance PES membranes' functionality by providing anti-fouling protection and imparting antimicrobial properties suitable for more complex water treatment environments. In this pursuit, Abid et al [58] fabricated PES ultrafiltration membranes through a phase change method using varied concentrations of APTMS (3-Aminopropyltrimthoxysilane) modified activated carbon (mAC) (Figure 5c). The resulting mAC membranes revealed enhanced hydrophilicity, reduced contact angle, improved porosity, roughness, water retention, and heightened water flux.…”
Section: Antimicrobial and Anti-fouling Self-cleaning Of Pes Fiber Me...mentioning
confidence: 99%
“…The anti-fouling studies using BSA solution filtration demonstrated that the mAC membrane exhibited favorable BSA flux rates. [54], schematic diagram of PES ultrafiltration membrane prepared using the phase change method (c) [58], schematic representation of PES-Ni@UiO-66 membranes prepared using an in situ reduction reaction (d) [59], pictures of the removal of 2,4,6-TCP via HPEI/MWCNTs/Fe-Cu/PES membranes (e) [55].…”
Section: Antimicrobial and Anti-fouling Self-cleaning Of Pes Fiber Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chang et al [24], adding carboxyl functional groups to the surface of activated carbon caused the carbon particles to become activated. To eliminate metal ions and other impurities, a hydrochloric solution (10% v/v) solution was fir s t used to clean the activated carbon powder for 24 hours.…”
Section: Activated Carbon Surface Modificationmentioning
confidence: 99%
“…To address this challenge, several studies have explored integrated PAC/polymer membranes for water treatment applications. For example, Abid et al (2022) used polyester sulfone and modified AC to prepare a UF membrane and reported that 28% carbon gave the best antibacterial performance. Using 3.6% PAC in a polyvinylidene fluoride (PVDF) membrane improved flux and chemical oxygen demand removal (Abuabdou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%